(untitled) (Journal of the College of Basic Education, 2022)
The study dealt with the phenotypic and histological aspects of the next brain, which included two parts: the pons and the cerebellum of female kestrels. The results of the morphology showed that the pons is a ganglion-like structure consisting of the peduncle and the base and innervated by four pairs of cranial nerves. The cerebellum was distinguished by being many folds and of the type of tubercle expanding from the front and the back. The anterior lobe of the cerebellum appeared of a small size and a slight elevation at the level of the first three cerebellar leaves. The posterior lobe of the cerebellum is broader and higher than the anterior lobe. The nodular flocculent lobe included the flocculent and the additional flocculent. The auricle was of a dome-like type at the base and tapering at the end.